Qualidade de vida em indivíduos iniciando a terapia antirretroviral utilizando esquemas de primeira linha - Gabriela Sales Pimentel (2019)
Quality of life (QoL) as a parameter of health assessment, as well as its associated factors, have been developing a extremely useful variable to demonstrate possible therapeutic interventions, especially in people living with HIV (PLWH). The objective of this study was longitudinally evaluate the change in QoL in PLWH starting antiretroviral therapy (ART) with first-line schemes attended in three public services reference in HIV/aids care in Belo Horizonte. A prospective cohort study was carried out, with the follow-up of individuals with HIV/aids, aged 13 years or over, minimum autonomy to answer the interview and in the use of antiretroviral drugs. Sociodemographic, behavioral and clinical data, related to pharmacologic treatment and to the service were obtained by interviews and supplemented by information from individuals´ medical records and information systems of Brazilian HIV/aids Program: Logistic Control System of Medicines (SICLOM) and Laboratory Test Control System (SISCEL). The change in QoL was assessed using the WHOQOLHIV-bref instrument and the associated factors were assessed using multiple linear regression. The quality of life’s domain with highest mean difference between the second follow-up interview and basal interview was the physical domain, which may have been provided by the use of ART, with probable changes in the course of HIV virus infection, while the domain with the lowest mean difference between the interviews was the social relationships domain. Patients on initiation of ART with first-line schemes presented an increase in QOL, being that have spiritual belief, treatment time equal to or less than 60 days and live with other people were positively associated with QOL, while having signs or symptoms of anxiety or depression was a predictor associated with worst QoL. The results evidence that the use of ART was associated with an increase in QoL global score in initial months of treatment. These results add new knowledge about the QoL of PLWH in Brazil, and can be used for the planning of scientific interventions and health promotion actions related to QoL.